Cardiac Tissue Characterization with Ultrasound and : a very early index of diabetic cardiomyopathy? - Yeneir Vera Fernández; Angela Castro Arca; Gerardo Senra; Emilio F Buchaca Faxas; Nicolás A Hernández (Medisur)
Introduction: There is an intrinsec myocardiopaty related with the diabetes and probably produced for the increment of collagen in the myocardium. Objective: To value the paper of the tissular myocardial characterization by ultrasound and the detection of diastolic dysfunction by pulsated Doppler as precocious indexes of diabetic miocardiopaty. Methods: Transverse, prospective,and controlled study that analyzed the diastolic function with pulsated Doppler in 60 diabetic patients and a control group of 15 healthy individuals; all with a normal pressure, with a negative ergometric test and normal systolic function; 40 presented microvascular complications. The securities of magnitude of recurrent variation were determined at the level of the septum and the posterior wall. The echocardiograms were carried out with the equipment ALOKA 5500 with a multiband transducer of 2.5 MHZ using the beta digital handling program (DMS) and the power Doppler in ecocardiografic views. Results: Reduction of the recurrent variation was obtained in diabetics with respect to the control group at the level of the septum 2D (3.4 ±1.3 vs. 4.4 ± 0.4 dB; p < 0.003) and the posterior wall PP2D (3.4 ± 1.3 vs. 6.2 ± 0.4 dB; p < 0.000001). Was found a correlation between the presence of diastolic dysfunction and the low magnitudes of ciclic variation (p < 0.001). The tissular characterization was more sensitive to detect precocious changes of the myocardium in diabetic patients (p < 0.001). Conclusions: The diabetes mellitus is cause of myocardiopaties that originate very precocious alterations in the myocardium of these patients; these changes can be discovered in very early phases by the pulsated Doppler detecting diastolic dysfunction and the tissular characterization by ultrasounds. This last one is more sensitive for the diagnosis of this entity.